Am 24.02.2012 11:17, schrieb firstname.lastname@example.org: > Hmmm! Tried following this approach, i.e. solving f(b)=0 with Netwon's and then plugging b in a=g(b), but it doesn't work. The solution doesn't satisfy the initial system. Try for example > > L=-1 > U=1 > p=0.0013498980316301 > > I get > > a=-1 > b=1 > > which clearly is wrong, i.e., a and b don't solve the initial system, even though f(b)=f(1)=0 and a=g(b)=g(1)=-1. I rewrite the initial system here: > > ((a-L)^2/a)*(2/(a+b))-p=0 > ((b-U)^2/b)*(2/(a+b))-p=0 > > Am I doing something wrong, or is FriCAS/Derive solution wrong?
When L=-U, you probably want p>1 to get a real result for a= (-2 U + 2 p U +/- sqrt((-1 + p) p^2 U^2))/((-2 + p) (-1 + p))